2020
DOI: 10.31234/osf.io/95qd3
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Profiles of Childhood Psychological Abuse and Neglect among Chinese College Students and Their Problematic Online Behaviors

Abstract: Background: Studies have shown that multiple forms of abuse may co-occur, resulting in specific abuse typologies. However, there is little understanding of complex interrelations of the different psychological abuse subgroups and internet game addiction and cyber-bullying. Objective: The objective of this study was to identify latent profiles of childhood psychological abuse and neglect among Chinese college students. Further, this study sought to examine the demographic characteristics of these profiles and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 29 publications
(36 reference statements)
0
3
0
Order By: Relevance
“…In China, males are often preached values of strength and traditional masculinity (e.g., “a man should strengthen himself [ ],” “real men do not easily cry [ ]”) and given lower emotional attention from parents during childhood development ( Ye et al, 2020 ). Thus, one possibility may be that males may find it more difficult to utilize their families as resources for stress management compared to females who may readily receive more emotional support ( Ye et al, 2020 ) and cope through productive dialogue ( Tamres et al, 2002 ). This echoes the ongoing issue of toxic masculinity in negative mental health outcomes ( Parent et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In China, males are often preached values of strength and traditional masculinity (e.g., “a man should strengthen himself [ ],” “real men do not easily cry [ ]”) and given lower emotional attention from parents during childhood development ( Ye et al, 2020 ). Thus, one possibility may be that males may find it more difficult to utilize their families as resources for stress management compared to females who may readily receive more emotional support ( Ye et al, 2020 ) and cope through productive dialogue ( Tamres et al, 2002 ). This echoes the ongoing issue of toxic masculinity in negative mental health outcomes ( Parent et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…This echoes the ongoing issue of toxic masculinity in negative mental health outcomes ( Parent et al, 2019 ). Although the topic of toxic masculinity in China has been given less attention than in their Western neighbors, recent evidence has alluded to the prevalence of gender differences in how males and females are given familial attention and support (e.g., Ye et al, 2020 ). Should males be more hesitant in seeking adaptive coping strategies, it may be worth examining alternative modes with which they can obtain proper resources anonymously online to not incur any cultural or social backlash.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have found that there is a low positive correlation between CT and PIU in coastal areas ( Hu et al, 2021 ), but other studies have found that there is a moderate positive correlation between CT and PIU in coastal areas ( Hou et al, 2021b ). In researches of non-coastal areas, some studies have found that CT and PIU are positively correlated to a low degree ( Li Y. et al, 2021 ), while some studies have found that CT and PIU are positively correlated to a moderate degree ( Ye et al, 2020 ; Cao et al, 2021 ). However, some studies also found a moderately high positive correlation between CT and PIU ( Dong et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%